Home Ground and Foreign Territory : Essays on Early Canadian Literature. - Fiamengo, Janice (Re-appraisals, Canadian writers., 2014)
Home Ground and Foreign Territory is an original collection of essays on early Canadian literature in English. Aiming to be both provocative and scholarly, it encompasses a variety of (sometimes opposing) perspectives, subjects, and methods, with the aim of reassessing the field, unearthing neglected texts, and proposing new approaches to canonical authors. Renowned experts in early Canadian literary studies, including D.M.R. Bentley, Mary Jane Edwards, and Carole Gerson, join emerging scholars in a collection distinguished by its clarity of argument and breadth of reference. Together, the es.